Pseudolymphomatous Cutaneous Reaction To Tick Bite - Sarkar Rashmi; Thami Gurvinder P; Kanwar Amrinder J (Wolters Kluwer Medknow Publications, 2001)
A case of pseudolymphomatous reaction to tick bite is being reported for its rarity. Slow removal of tick sticking to the skin is being emphasized for avoiding such reactions to tick bite.